Angiotensin receptor neprilysin inhibitor for patients with heart failure and reduced ejection fraction: Real-world experience from Turkey (ARNi-TR) - Ekici, Berkay; Yaman, Mehmet; Kucuk, Murathan; Dereli, Seckin; Yenercag, Mustafa; Yigit, Zerrin; Zoghi, Mehdi (Kare Publ, 2021)
Objective: Heart failure (HF) is a growing public health problem with high morbidity and mortality. Recently, angiotensin receptor neprilysin inhibitor (ARNi) has emerged as a promising treatment for HF with reduced ejection fraction (HFrEF). Here, we shared our experience with the use of ARNi in HFrEF from multiple centers in Turkey. Methods: The ARNi-TR is a multicenter, nonintervention al, retrospective, observational study. Overall, 779 patients with HF from 22 centers in Turkey who were prescribed sacubitril/valsartan were examined. Initial clinical status, biochemical and echocardiographic parameters, and New York Heart Association functional class (NYHA-FC) values were compared with follow-up values after 1 year of ARNi use. In addition, the effect of ARNi on number of annual hospitalizations was investigated, and the patients were divided into 2 groups, depending on whether ARNi was initiated at hospitalization or under outpatient clinic control. Results: N-terminal pro-brain natriuretic peptide (NT-proBNP), left-ventricle ejection fraction (LV-EF), and NYHA-FC values improved significantly in both groups (all parameters, p<0.001) within 1-year follow-up. In both groups, a decrease in hemoglobin A1c (HbA1c) values was observed in ARNi use (p<0.001), and a decrease in daily diuretic doses and hospitalizations owing to HF were observed after ARNi use (all comparisons, p<0.001). Hypotension (16.9%) was the most common side effect in patients using ARNi. Conclusion: The ARNi-TR study offers comprehensive real-life data for patients using ARNi in Turkey. The use of ARNi has shown significant improvements in FC, NT-proBNP, HbA1c levels, and LV-EF. Likewise, reductions in the number of annual hospitalizations and daily furosemide doses for HF were seen in this study.
Keywords: Angiotensin receptor neprilysin inhibitor; heart failure with reduced ejection fraction; sacubitril; valsartan; real-world